Desecrating the Sacred: A Study of Criminal Liability for Graveyard Vandalism in Yogyakarta - Isnawan, Fuadi (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
Public cemeteries (TPU) serve not only as burial sites for the deceased, but also as symbols of final respect for those who have passed away. The state, through legislation, provides legal protection for the deceased and their graves, prohibiting any actions that insult or damage their dignity. However, the case of grave desecration that occurred in Yogyakarta in May 2025, involving a teenager with the initials ANF (16), caused social unrest and sparked academic discussion regarding criminal liability for such actions. This study uses a normative method to analyze the legal aspects of the criminal act of grave desecration based on Article 179 of the Criminal Code. The results of the study indicate that the perpetrator's actions fulfilled the elements of the offense, namely intentional acts without authority that caused physical damage to the grave as a legal object with high symbolic and spiritual value. Although the perpetrator is still a minor, he can still be held criminally liable under the juvenile criminal justice system, with the application of restorative justice principles. Additionally, the role of the Indonesian National Police in preventing and addressing this criminal act is crucial, encompassing preventive, repressive, and coordinative efforts to maintain social stability and respect the legal and cultural values of society. This study emphasizes the importance of legal protection for graves and remains as a manifestation of respect and dignity for humanity that must be upheld collectively.